Harvesting rice's dispensable genome. Issue 1 (December 2015) - Wing, Rod
Abstract A rapid and cost-effective approach has been developed to harvest and map the dispensable genome, that is, population-level natural sequence variation within a species that is not present in static genome assemblies. See related Research article:http://www.genomebiology.com/2015/16/1/187 .